Sharp-Wave Ripple Frequency and Interictal Epileptic Discharges Increase in Tandem During Thermal Induction of Seizures in a Mouse Model of Genetic Epilepsy - Cheah, Christine S.; Beckman, Megan A.; Catterall, William A.; Oakley, John C. (Frontiers in Cellular Neuroscience, 2021)
Dravet Syndrome (DS) is a genetic, infantile-onset epilepsy with refractory seizures and severe cognitive impairment. While network level pathophysiology is poorly understood, work in genetic mouse models of DS reveals selective reduction of inhibitory interneuron excitability, a likely mechanism of seizures and comorbidities. Consistent with the critical role of interneurons in timing and recruitment of network activity, hippocampal sharp wave ripples (SPW-R)—interneuron dependent compound brain rhythms essential for spatial learning and memory—are less frequent and ripple frequency is slower in DS mice, both likely to impair cognitive performance. Febrile seizures are characteristic of DS, reflecting a temperature-dependent shift in excitation–inhibition balance. DS interneurons are sensitive to depolarization block and may fall silent with increased excitation precipitating epileptic transformation of ripples. To determine the temperature dependence of SWP-R features and relationship of SPW-R to hippocampal interictal activity, we recorded hippocampal local field potentials in a DS mouse model and wildtype littermate controls while increasing core body temperature. In both genotypes, temperature elevation speeds ripple frequency, although DS ripples remain consistently slower. The rate of SPW-R also increases in both genotypes but subsequently falls in DS mice as interictal epileptic activity simultaneously increases preceding a thermally-evoked seizure. Epileptic events occur intermixed with SPW-R, some during SPW-R burst complexes, and transiently suppress SPW-R occurrence suggesting shared network elements. Together these data demonstrate a temperature dependence of SPW-R rate and ripple frequency and suggest a pathophysiologic mechanism by which elevated temperature transforms a normal brain rhythm into epileptic event.